The cost‐benefit of using soft silicone multilayered foam dressings to prevent sacral and heel pressure ulcers in trauma and critically ill patients: a within‐trial analysis of the Border Trial. Issue 3 (6th October 2013) - Santamaria, Nick; Liu, Wei; Gerdtz, Marie; Sage, Sarah; McCann, Jane; Freeman, Amy; Vassiliou, Theresa; DeVincentis, Stephanie; Ng, Ai W; Manias, Elizabeth; Knott, Jonathan; Liew, Danny
Abstract Little is known about the cost‐benefit of soft silicone foam dressings in pressure ulcer (PU) prevention among critically ill patients in the emergency department (ED) and intensive care unit (ICU). A randomised controlled trial to assess the efficacy of soft silicone foam dressings in preventing sacral and heel PUs was undertaken among 440 critically ill patients in an acute care hospital. Participants were randomly allocated either to an intervention group with prophylactic dressings applied to the sacrum and heels in the ED and changed every 3 days in the ICU or to a control group with standard PU prevention care provided during their ED and ICU stay. The results showed a significant reduction of PU incidence rates in the intervention group (P = 0·001). The intervention cost was estimated to be AU36·61 per person based on an intention‐to‐treat analysis, but this was offset by lower downstream costs associated with PU treatment (AU1103·52). Therefore, the average net cost of the intervention was lower than that of the control (AU70·82 versus AU144·56). We conclude that the use of soft silicone multilayered foam dressings to prevent sacral and heel PUs among critically ill patients results in cost savings in the acute care hospital.